Job Hopping Behaviour and Turnover Intention on Millennial Teachers: A Closer Look to Their Antecendents - Juliana Juliana; Suwarto Suwarto; Rudy Pramono; Martinus Tukiran (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: Job Hopping Behaviour and Turnover Intention on Millennial Teachers: A Closer Look to Their AntecedentsThe purpose of this research is to examine the impacts of job satisfaction, psychological capital and perceived organizational support on the turnover intention or job-hopping behaviour among millennial teachers. The data collection is done by having a survey using questionnaires sent to 86 teachers who belong to the millennial group age and have been working between one to three years in the respective schools. A quantitative approach was used using the PLS-SEM method with the assistance of Smart PLS 3.2.7 software to evaluate the outer model and the inner model. The results show that there are negative significant effects from perceived organizational support and psychological capital on turnover intention or job-hopping behaviour and no significant effect from the job satisfaction on the turnover intention of the millennial teachers..Abstract: Analisis Faktor Pemicu Perilaku Job Hopping Dan Intensi Berpindah Tempat Kerja Pada Guru MilenialTujuan dari penelitian ini adalah untuk menguji pengaruh kepuasan kerja, psychological capital dan persepsi dukungan organisasi terhadap keinginan berpindah kerja dan perilaku job-hopping di kalangan guru milenial. Pengumpulan data dilakukan dengan survei menggunakan kuesioner yang dikirimkan kepada 86 guru yang merupakan kelompok usia milenial dan telah bekerja selama kurin waktu satu sampai tiga tahun di lembaga pendidikan tempat mereka bernaung. Pendekatan kuantitatif menggunakan metode PLS-SEM dengan bantuan software Smart PLS 3.2.7 untuk mengevaluasi outer model dan inner model. Hasilnya menunjukkan bahwa terdapat pengaruh negatif signifikan dari persepsi dukungan organisasi dan modal psikologis terhadap perilaku berpindah tempat kerja dan tidak ada pengaruh signifikan dari kepuasan kerja terhadap perilaku berpindah tempat kerja dari para pengajar generasi milenial.